Karakterisasi Anggrek Alam secara Morfologi dalam Rangka Pelestarian Plasma Nutfah - Hartati, Sri; Darsana, Linayanti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTMorphological characters of natural orchids (species) is an important key for successful breeding program of orchids. This study was aimed to determine the morphological diversity and to study the genetic relationship among natural orchids from Java. The characterization was conducted on 12 orchids collected from Central, East and West Java from April to September 2012. Twenty five characters including stem, leaves, flower, pseudobulb, and root type were evaluated and scored based on Guidance of Orchid Characterization. Cluster analysis was done using the NTSYSpc version 2.02i under UPGMA function of SimQual. The study showed that there was a diversity on morphology of stem, pseudo bulb, leaf, flower and root type. Dendrogram based on genetic similarity at 52% clustered the population into two groups. The first group consisted of Paphiopedilum purpurascens, P. javanicum, P. glaucophylum, Coelogyne flexuosa, C. spesiosa, Dendrobium mutabile. Bulbophyllum blumei and B. biflorum. The second group was Coelogyne tomentosa, C. trinervis, D. crumenatum, and B. flavescens LindlKeywords: cluster analysis, dendrogram, diversity, morphology